The Role of Information Systems in Integrating the Supply Chain in the General Company for Gas Filling and Services - Alzeaer, Fatima Ali Majeed; Alsaker, Ghufran Jbarah Lafta (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
This study aimed to measure the role of information systems as an independent variable with its dimensions represented by (human resources, equipment and devices, software, data sources, networks and communications) on supply chain integration as a dependent variable with its dimensions (customer, source, manufacture, delivery, returns) and in order to achieve Objective of the study: Two main sources were relied upon to collect the data necessary for this study: secondary data sources, which included the Internet, periodicals, references, and a review of literature related to the study, to explain the basic concepts and identify the most important studies that addressed the subject of the study, while the primary data sources included the analysis of 65 questionnaires distributed Employees of the General Company for Gas Filling and Services / Basra Branch were randomly selected, and the statistical program SPSS was used to analyze the data.The researcher reached several conclusions, most notably the existence of a statistically significant impact relationship between information systems and supply chain integration. Based on the results, the research presented a set of recommendations, the most prominent of which is the study recommends to the General Company for Gas Filling and Services/Basra the importance of continuing to learn about the concept of information systems and the necessity of applying them in the ongoing competition processes. The company's ability to implement information systems in an appropriate manner gives it greater flexibility in facing environmental challenges.